Glucagon-like peptide-1 receptor is involved in learning and neuroprotection - During, Matthew J.; Klugmann, Matthias (Nature medicine, 2003)
Glucagon-like peptide-1 (GLP-1) is a gut peptide that, together with its receptor, GLP-1R, is expressed in the brain. Here we show that intracerebroventricular (i.c.v.) GLP-1 and [Ser(2)]exendin(1−9) (HSEGTFTSD; homologous to a conserved domain in the glucagon/GLP-1 family) enhance associative and spatial learning through GLP-1R. [Ser(2)]exendin(1−9), but not GLP-1, is also active when administered peripherally. GLP-1R-deficient mice have a phenotype characterized by a learning deficit that is restored after hippocampal Glp1r gene transfer. In addition, rats overexpressing GLP-1R in the hippocampus show improved learning and memory. GLP-1R-deficient mice also have enhanced seizure severity and neuronal injury after kainate administration, with an intermediate phenotype in heterozygotes and phenotypic correction after Glp1r gene transfer in hippocampal somatic cells. Systemic administration of [Ser(2)]exendin(1−9) in wild-type animals prevents kainate-induced apoptosis of hippocampal neurons. Brain GLP-1R represents a promising new target for both cognitive-enhancing and neuroprotective agents.
Gesehen am 08.06.2017